Maximum strength & strength training - relationship to endurance? - Stone, M.; Carlock, J.; Stone, M. (coachesinfo.com, 2002)
The purpose of this brief review is to consider the association of measures of maximum strength in relation to sport performance endurance and endurance related factors. Evidence from different types of cross-sectional research as well as observational data was considered. Collectively the data indicate that the association between maximum strength and sport performance endurance factors is stronger then might be expected. While, explaining performance/endurance in sports is a multi-factorial problem there is little doubt that maximum strength is a key component. Summary Part 1: Although not all studies agree the data presented indicate that: 1. Although specificity is evident, strength training can produce adaptations in endurance, which is "transferable", i.e. adaptations can take place in exercises not used in the strength-training program. 2. Higher volume training can affect measures of endurance to a greater extent than low volume training. 3. Within the context of strength-training short rest periods (< 90 s) do not enhance endurance beyond using typical rest periods and can compromise strength and power gains. If rest periods are too short (< 30 s) loading may be compromised sufficiently to result in smaller gains in strength power and possibly HIEE. Summary Part 2: These data suggests that: 1. Maximum strength can be associated with LIEE. 2. Strength training can improve LIEE or factors associated with LIEE. 3. As with strength/power sports there is a degree of specificity in the endurance adaptations. Based on this brief review, the authors suggest that: 1. Maximum Strength is associated with endurance factors - the association is likely stronger for HIEE activities than for LIEE. 2. Strength training can affect increases in endurance factors for both HIEE and LIEE. 3. The volume of strength training plays a role in the endurance adaptation (i.e. higher volumes generally produce greater gains in endurance). 4. Mechanical specificity and training programme variables also play a role in the degree of adaptation.